Identification and physicochemical characterization of 4‐fluorobutyrfentanyl (1‐((4‐fluorophenyl)(1‐phenethylpiperidin‐4‐yl)amino)butan‐1‐one, 4‐FBF) in seized materials and post‐mortem biological samples. Issue 3 (29th December 2016) - Rojkiewicz, Marcin; Majchrzak, Milena; Celiński, Rafał; Kuś, Piotr; Sajewicz, Mieczysław
Abstract : During the last decade, a substantial growth in new psychoactive substances (NPS) has been recorded. Within this group, a considerably fast‐growing sub‐group is represented by the opioids, which are based on modifications of the fentanyl structure. In this study, identification and analytical characterization of a new fentanyl derivative, 4‐fluorobutyrfentanyl (1‐((4‐fluorophenyl)(1‐phenethylpiperidin‐4‐yl)amino)butan‐1‐one, 4‐FBF), is described. Apart from the seized powder, 4‐FBF was also identified in the e‐cigarette liquid secured in Case 1. The concentration of the compound in the liquid was 35 mg/mL. The main component of the liquid was glycerol, and nicotine was also present. This substance was detected in seized material that originated from the illegal drug market in Poland. To the best of the authors' knowledge, this report presents the first two analytically confirmed cases of fatal intoxication associated with 4‐FBF. Case 1 was a 26‐year‐old male drug user who was found dead at home. Case 2 was a 25‐year‐old female, occasional user of NPS and drugs, who was also found dead at home. The concentrations of 4‐FBF in blood were 91 and 112 ng/mL and in urine 200 and 414 ng/mL. The concentrations of 4‐FBF in liver and kidney were 902 and 411 ng/g, and 136 and 197 ng/g, for Case 1 and Case 2, respectively. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Among the synthetic opioids used for non‐medical purposes in the course of the last decade, the fentanyl derivatives are most prominent and all these compounds have contributed to numerous lethal intoxications. In this study, the identification and analytical characterization of 4‐FBF is presented, together with the detection in two lethal intoxication cases.